(untitled) (Citizenship in Action: Extension and Culture Magazine, 2023)
Discusses the podcast as a tool for the democratization of knowledge and scientific dissemination. Does it aim to report the performance of the Biblioque Podcast? as an instrument for the production of dissemination of situational information about the Pandemic. This is an experience report of the execution of a university extension project, at the Federal University of Amazonas, by professors and students of the Librarianship course. It analyzes that (i) university extension can work as a means to provide society with situational information with a view to combating fake news and misinformation, being efficient in times of crisis such as the new coronavirus pandemic; (ii) the pandemic highlighted several problems in society, in various spheres, among them, the still deficient use of information and communication technologies; (iii) the contents with the highest audience were related to the report of confinement (which brought content about mental health, readings, reflections and support network) (36.5%) and Competence in situational information (29.9%). It concludes that the scripting of the special episodes was able to fulfill the proposal, reaching its audience, by exercising the role of informing and communicating the academic community and society about the changes and consequences caused by the new Coronavirus.